Вчинення консулом нотаріальних дій, що пов’язані з сімейними відносинами - Чекіта, Віоланта Геннадіївна; Чекита, Виоланта Геннадьевна; Chekita, Violanta G. (My University, 2018)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.03 - цивільне право і цивільний процес; сімейне право; міжнародне приватне право. - Національний університет «Одеська юридична академія», Одеса, 2018. Дисертацію присвячено дослідженню правової регламентації вчинення консулом нотаріальних дій, що пов’язані з сімейними відносинами. У роботі шляхом узагальнення досвіду, накопиченого консульськими установами України, досліджено сучасний стан чинного законодавства України, що регламентує як організаційно-правові, так й процесуальні аспекти вчинення консулами нотаріальних дій з метою охорони та захисту прав громадян України та юридичних осіб, які знаходяться за кордоном; розкрито особливості процедури вчинення консулом нотаріальних проваджень, що пов’язані з сімейними відносинами, обґрунтовано пропозиції, спрямовані на вдосконалення законодавства щодо вчинення консулом нотаріальних проваджень. У роботі проаналізовано повноваження консула, особливості його діяльності в світлі міжнародних договорів, законодавства акредитуючої країни та держави перебування консула. Багато уваги приділено уточненню і конкретизації процедури діяльності консула, особливостям посвідчення найбільш важливих нотаріальних проваджень. Розглянуто теоретичні підходи до нотаріальної діяльності консула, проаналізовані джерела правового регулювання нотаріальної діяльності консула. Досліджено процедури нотаріального посвідчення консулом договорів про поділ майна подружжя як інструменту правового регулювання відповідних сімейних відносин, визначено особливості його складання, процедури нотаріального посвідчення консулом. Сформульовано науково обґрунтовані пропозиції з удосконалення теорії нотаріального процесу, законодавства, що регламентує діяльність консула з учинення нотаріальних дій щодо посвідчення сімейних правочинів.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.03 - гражданское право и гражданский процесс; семейное право; международное частное право. - Национальный университет «Одесская юридическая академия», Одесса, 2018. Диссертация посвящена исследованию правовой регламентации совершения консулом нотариальных действий, связанных с семейными отношениями. В работе путем обобщения опыта, накопленного консульскими учреждениями Украины, исследовано современное состояние действующего законодательства Украины, регламентирующего как организационно-правовые, так и процессуальные аспекты совершения консулами нотариальных действий с целью охраны и защиты прав граждан Украины и юридических лиц, находящихся за рубежом; раскрыты особенности процедуры совершения консулом нотариальных производств, связанных с семейными отношениями, обоснованы предложения, направленные на совершенствование законодательства в отношении совершения консулом нотариальных производств. В работе проанализированы полномочия консула, особенности его деятельности в свете международных договоров, законодательства представляемого государства и государства пребывания консула. Много внимания уделено уточнению и конкретизации процедуры деятельности консула, особенностям удостоверения наиболее важных нотариальных производств. Рассмотрены теоретические подходы к нотариальной деятельности консула, проанализированы источники правового регулирования нотариальной деятельности консула. Автором рассмотрены процедуры нотариального удостоверения консулом договоров о разделе имущества супругов как инструмента правового регулирования соответствующих семейных правоотношений, определены особенности его составления, процедуры нотариального удостоверения консулом. Сформулированы научно обоснованные предложения по совершенствованию теории нотариального процесса, законодательства, регламентирующего деятельность консула по совершению нотариальных действий в отношении удостоверения семейных сделок.

Thesis for a Candidate Degree in Law, specialty 12.00.03 «Civil Law and Civil Procedure; family law; international private law» (081 - Law). - National University «Odesa Law Academy», Odesa, 2018. The dissertation is one of the first in the national science of the notary process of special complex research of theoretical and practical problems of the procedure of making the notary activities related to family relations to the Consul. In this work, by summarizing the experience gained by the consular institutions of Ukraine, the current state of the current legislation of Ukraine is examined, which regulates both organizational and legal aspects as well as procedural aspects of the consular officers’ work of notarial acts in order to protect and protect the rights of citizens of Ukraine and legal entities who are abroad; The peculiarities of the procedure for making the consular service of notarial proceedings related to family relations are revealed, the proposals aimed at improving the legislation concerning the Consul of the Notary Proceedings are substantiated. The powers of the consul, peculiarities of his activity in the light of international treaties, legislation of the accrediting country and the consulate state are analyzed. Much attention is paid to the clarification and specification of the procedure of the consul, especially the certification of the most important notarial proceedings. The theoretical approaches to the consulate’s notarial activity are considered, sources of legal regulation of the consular’s notarial activity are analyzed. The procedure of notarial certification by the consul of agreements on the division of property of the spouses as an instrument of legal regulation of the relevant family relations is explored, features of its drafting, procedure of notary certification by the consul are determined. The dissertation proposes to determine the notarial function of the consul as an element of the state function for ensuring the rights of individuals and legal entities of Ukraine who are in the territory of a foreign country or whose interests relate to objects in a foreign country, legal assistance, which includes notarial services for the guaranteed realization of their own rights and fulfillment of duties assigned to them. In the dissertation, in order to eliminate the terminological shortcomings of the current legislation of Ukraine, the activities of consuls in the course of committing notarial acts in the sphere of family relations are understood to mean fixing in the treaties and other notarial acts the free and informed wills of the family members, corresponding to their internal will and aimed at the emergence , change or termination of personal non-property and / or property rights and responsibilities in the family sphere; under family law, to understand the actions of individuals related to family law status (spouses, parents and children, other family members and relatives, etc.) which, in addition to the circumstances listed, include the exercise of rights and duties, self-defense of family rights, treatment to court and so on. The necessity of creating a state program for generalization and analysis of problem issues related to family relations with a foreign element is proved. In order to specify such relations in the treaties and to determine the permissible conditions of a marriage contract, the concept of “moral principles of Ukrainian society” should 20 be disclosed, as well as the judicial practice in foreign countries where the rights of citizens of Ukraine represented or ensure the representation of their interests were consuls. The notion of “notarial proceedings carried out by the consul” is formulated as a set of consecutive notarial procedural actions carried out by the consul to provide certain facts of legal certainty and their proper execution. Concerning the activities of the Consul in the commission of notarial acts, the emphasis should be on its specific features, which are reduced to the fact that when the consuls explained their rights and responsibilities, the warning of the consequences of the notarial acts being performed in order to prevent legal ignorance to be used at his own expense, explanations should be provided on the application of notarial acts both on the territory of Ukraine and, in certain cases, in the territory of a foreign country and / or the commonwealth of European countries. In the dissertation, the following is proposed as a “procedure for making the consular officer of notarial proceedings”: 1) a set of means and methods of carrying out the notary’s duties, which must be in accordance with his powers in a particular country of residence, and comply with the provisions of the legislation of Ukraine, a foreign country and the conditions of international agreements; 2) the officially established procedure for the implementation of the rules and norms of the Consular Notary’s activities, fixed in the legislation of Ukraine; 3) the activities of the consul in relation to the performance of notarial acts, the result of which should be the protection and protection of the rights and interests of individuals and legal entities of Ukraine abroad, who apply to the consul for the performance of notarial acts. It is established that from a legal point of view, procedural issues of the consulate’s certification of alimony contracts, in which one of the parties is a foreigner, is established. When certifying the alimony contract, the consul, in addition to the norms of national law, should also take into account the rules of the foreign law of the host State regarding the content of such an agreement. Normatively established procedure for the notarial certification by the consul of the alumni contract requires more certainty. Established by the Regulation on the procedure for the performance of notarial acts in diplomatic missions and consular offices of Ukraine, special rules cover only a small number of issues related to the certification of alimony contracts, and in most cases do not take into account their features. At the same time, the features of the notarial certificate by the consul of the agreement on payment of child support should be properly reflected in the procedural aspects of the consul’s activities, in particular, in order to find out the compliance of the content and terms of such agreement with the substantive law of Ukraine and a foreign country. Scientificly substantiated proposals on improving the theory of the notarial process, the legislation regulating the activities of the consul on the performance of notarial acts regarding the certification of family affairs, are formulated.
дис. ... канд. юрид. наук: 12.00.03
Чекіта В.Г. Вчинення консулом нотаріальних дій, що пов’язані з сімейними відносинами: дис. ... канд. юрид. наук: 12.00.03 / Чекіта Віоланта Геннадіївна. - Одеса, 2018. - 220 с.
Keywords: консул; нотаріальна дія; процедура нотаріального посвідчення; нотаріальне провадження; сімейні правовідносини; аліментний договір; договір про поділ майна подружжя; шлюбний договір; заповіт подружжя; нотариальное действие; процедура нотариального удостоверения; нотариальное производство; семейные правоотношения; алиментный договор; договор о разделе имущества супругов; брачный договор; завещание супругов; consul; notarial act; notarial procedure; notarial proceedings; family relations; alimony contract; agreement on the division of property of spouses; marriage contract; wills of spouses